At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To find all roots of the equation [tex]\(x^3 - 5x^2 + 4x = 0\)[/tex], we need to solve for [tex]\(x\)[/tex] such that the given equation is satisfied. Let’s follow a step-by-step approach:
1. Factorize the equation: The given equation is a polynomial equation. We will start by factoring it.
[tex]\[ x^3 - 5x^2 + 4x = 0 \][/tex]
Notice that each term on the left-hand side contains [tex]\(x\)[/tex]. Hence, we can factor out [tex]\(x\)[/tex]:
[tex]\[ x(x^2 - 5x + 4) = 0 \][/tex]
2. Solve the factored equation: Now we have a product of factors equal to zero. To satisfy this equation, at least one of the factors must be zero. We solve for [tex]\(x\)[/tex] from each factor separately.
[tex]\[ x = 0 \][/tex]
and
[tex]\[ x^2 - 5x + 4 = 0 \][/tex]
3. Solve the quadratic equation: Next, we solve [tex]\(x^2 - 5x + 4 = 0\)[/tex]. This is a standard quadratic equation, and we can solve it using the factorization method.
First, we look for two numbers that multiply to give the constant term (4) and add up to give the coefficient of the linear term (-5). Those numbers are -1 and -4.
So, we can write:
[tex]\[ x^2 - 5x + 4 = (x - 1)(x - 4) = 0 \][/tex]
4. Find the roots of the quadratic equation: Setting each factor equal to zero gives us the roots:
[tex]\[ x - 1 = 0 \quad \Rightarrow \quad x = 1 \][/tex]
[tex]\[ x - 4 = 0 \quad \Rightarrow \quad x = 4 \][/tex]
5. Compile all the roots: Combining the roots from our factors, we get:
[tex]\[ x = 0, \quad x = 1, \quad x = 4 \][/tex]
Thus, all the roots of the equation [tex]\(x^3 - 5x^2 + 4x = 0\)[/tex] are:
[tex]\[ x = 0, \quad x = 1, \quad x = 4 \][/tex]
1. Factorize the equation: The given equation is a polynomial equation. We will start by factoring it.
[tex]\[ x^3 - 5x^2 + 4x = 0 \][/tex]
Notice that each term on the left-hand side contains [tex]\(x\)[/tex]. Hence, we can factor out [tex]\(x\)[/tex]:
[tex]\[ x(x^2 - 5x + 4) = 0 \][/tex]
2. Solve the factored equation: Now we have a product of factors equal to zero. To satisfy this equation, at least one of the factors must be zero. We solve for [tex]\(x\)[/tex] from each factor separately.
[tex]\[ x = 0 \][/tex]
and
[tex]\[ x^2 - 5x + 4 = 0 \][/tex]
3. Solve the quadratic equation: Next, we solve [tex]\(x^2 - 5x + 4 = 0\)[/tex]. This is a standard quadratic equation, and we can solve it using the factorization method.
First, we look for two numbers that multiply to give the constant term (4) and add up to give the coefficient of the linear term (-5). Those numbers are -1 and -4.
So, we can write:
[tex]\[ x^2 - 5x + 4 = (x - 1)(x - 4) = 0 \][/tex]
4. Find the roots of the quadratic equation: Setting each factor equal to zero gives us the roots:
[tex]\[ x - 1 = 0 \quad \Rightarrow \quad x = 1 \][/tex]
[tex]\[ x - 4 = 0 \quad \Rightarrow \quad x = 4 \][/tex]
5. Compile all the roots: Combining the roots from our factors, we get:
[tex]\[ x = 0, \quad x = 1, \quad x = 4 \][/tex]
Thus, all the roots of the equation [tex]\(x^3 - 5x^2 + 4x = 0\)[/tex] are:
[tex]\[ x = 0, \quad x = 1, \quad x = 4 \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.